Mechanisms of γδ T cell accumulation in visceral adipose tissue with aging - Mukherjee, Sujata; Bruno, Maria E. C.; Oakes, Jason; Hawk, Gregory S.; Stromberg, Arnold J.; Cohen, Donald A.; Starr, Marlene E. (Frontiers in Aging, 2024)
 T cells are resident in visceral adipose tissue (VAT) where they show an age-associated increase in numbers and contribute to local and systemic chronic inflammation. However, regulation of this population and mechanisms for the age-dependent accumulation are not known. In this study, we identified a progressive trend of T cell accumulation in VAT over the lifespan in mice and explored physiological mechanisms contributing to accumulation. Using isochronic parabiotic pairs of wild-type (WT) and T cell receptor delta knockout (TCR KO) mice at young and old age, we confirmed that VAT  T cells are predominately a tissue-resident population which is sustained in aging. Migration of peripheral T cells into VAT was observed at less than 10%, with a decreasing trend by aging, suggesting a minor contribution of recruitment to  T cell accumulation with aging. Since tissue-resident T cell numbers are tightly regulated by a balance between proliferation and programmed cell death, we further explored these processes. Using in vivo EdU incorporation and the proliferation marker Ki67, we found that the absolute number of proliferating T cells in VAT is significantly higher in the aged compared to young and middle-aged mice, despite a decline in the proportion of proliferating to non-proliferating cells by age. Analysis of apoptosis via caspase 3/7 activation revealed that VAT  T cells show reduced apoptosis starting at middle age and continuing into old age. Further, induction of apoptosis using pharmacological inhibitors of Bcl2 family proteins revealed that VAT  T cells at middle age are uniquely protected from apoptosis via a mechanism independent of traditional anti-apoptotic Bcl2-family proteins. Collectively, these data indicate that protection from apoptosis at middle age increases survival of tissue-resident  T cells resulting in an increased number of proliferative cells from middle age onward, and leading to the age-associated accumulation of  T cells in VAT. These findings are important to better understand how adipose tissue dysfunction and related changes in the immune profile contribute to inflammaging among the elderly.